Bisexual Aunts, Gay Cousins: How LGBTQ Family Members Help LGBTQ Youth Navigate Family Heteronormativity. (August 2022) - Stone, Amy L.; Pride, Chiara; Adams, Benjamin; Salcido, Robert
There is little research on the impact of having LGBTQ family members on LGBTQ youth, despite a body of literature that emphasizes the importance of supportive family members for these youth. Using interviews with a racially diverse group of 26 LGBTQ youth in South Texas, the authors argue that LGBTQ family members, specifically nonparental relatives, play a supportive role in the lives of LGBTQ youth, particularly for Latinx youth. These family members help LGBTQ youth navigate family communication norms and practices around gender and sexuality, including insight into unspoken communication norms and translation for reading family interactions. The authors argue that these family members and their connections with LGBTQ youth were part of a broader resistance to heteronormativity within family life.